Perpustakaan Desa, Sarana Untuk Meningkatkan Minat Baca Bagi Anak-Anak Selama Pandemi - Shochifah Diyah Puspitasari; Wara Dyah Pita Rengga; Muhammad Arsa A D; Andrian Satria Oktafandy4 (Fakultas Dakwah dan Ilmu Komunikasi, 2021)
Abstract: The availability of reading books in the community is an important factor in encouraging the readability and interest of the community, including children, in reading interest. The availability of complete village library facilities and a variety of reading materials can encourage the community's interest in reading, including local children, to increase. With adequate facilities, it can also provide insight into the community and quality local children, as well as being a diversion from technology that lulls many children today. Based on the studies on these researches, this research has an important role in efforts to increase interest in reading in village children during the Covid-19 pandemic as it is today. In this study the authors used descriptive qualitative research methods. The data sources used in this study are children aged 7 to 15 years who live in rural areas. The existence of a village library with attractive supporting facilities can motivate children to visit the library, read books there, and enrich knowledge other than those obtained from the teacher in the learning process.